The attitudes of future pedagogists to sustainable development - Kalmar Laura (Pedagoško društvo Srbije i Institut za pedagogiju i andragogiju Filozofskog fakulteta Univerziteta u Beogradu, 2021)
Sustainable development is an essential precondition, and also the ultimate goal, of the organization of numerous human activities, with particular emphasis on education. One of the key dimensions of sustainable development is the social dimension, which refers to citizens' comprehension of its importance. The aim of the study presented in this paper was to establish the attitudes of future pedagogists towards sustainable development. The sample consisted of 240 respondents. The study used the descriptive method, and the data collection technique used was the questionnaire survey-the Questionnaire for the Assessment of Attitudes to Sustainable Development. The results of the survey confirm the general research hypothesis that students regard sustainable development as extremely important. Students of teacher training faculties are aware of the concept and importance of sustainable development for the present and the future, but are insufficiently prepared to educate future generations about it. The pedagogical implications of this study would be that university teachers should implement more content dealing with sustainable development as part of the curriculum, particularly at faculties educating future pedagogists. This is particularly important for these students so that they can act with the future in mind-the future of young generations.